Faktor-Faktor Yang Menjadi Permasalahan Dalam Pendaftaran Tanah Di Kelurahan Hutuo - Moh. Shafwan Saifullah Pakaya; Fence M.Wantu; Nirwan Junus (Jurnal Hukum dan Sosial Politik, 2024)
The aim of this research is to find out the process and implementation of land registration in Hutuo Village, as well as to find out the factors that cause problems in land registration in Hutuo Village. The type of research used is Empirical Legal research. Data collection techniques were carried out using interview techniques and literature. Then the writer will analyze the data obtained in the research process descriptively, in this case the researcher will describe the description of the research subjects and objects as the results of the research he conducted. The results of this research indicate that land registration in Hutuo Village in view of Government Regulation Number 24 of 1997 is still not optimal. This is proven by the data in Hutuo Village where there are still a large number of unregistered land cases. However, the cases of land that have not been registered have not been resolved, due to the background obstacles that influence the achievement of legal certainty in the Hutuo Village. The suggestion in this research is that the Government, especially the Regional Office of the National Land Agency in Gorontalo Regency, continues to strive to carry out more outreach to the people of Hutuo Subdistrict to carry out land registration so that they can have a certificate to obtain legal certainty.